FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Sherly Liana; Riki Sanjaya (E-Jurnal Akuntansi TSM, 2022)
This research aims to analyse and obtain empirical evidence about the influence of independent variables on Firm value. The independent variables tested in this research were Managerial Ownership, Institutional Ownership, Company Growth, Return on Asset (ROA), Debt to Asset Ratio, Liquidity and Firm Size. The sample of this research consisted 103 non-financial company that had been listing in Indonesia Stock Exchange from 2018 to 2020. The sample chosen is by using purposive sampling method and the hypothesis is tested by using multiple regression analysis. The result showed that ROA and Debt to Asset Ratio had influence on Firm value. Meanwhile, the other five variables namely Managerial Ownership, Institutional Ownership, Company Growth, Liquidity and Firm Size had no influence on Firm value.